Burning Mouth Syndrome due to Television Moans, an Enigma for Oral Physician: Treatment with Counseling - Gupta, Deepak (Tabriz University of Medical Sciences, 2014)
Burning mouth syndrome (BMS) is a relatively common disease that can severely affect the quality of life of the patient. It causes chronic orofacial pain or oral burning sensation even in the absence of any detectable organic cause. The etiology of BMS is complex and multifactorial. It has been associated with menopause, trigger events and even genetic polymorphisms. Although its etiology remains unclear, there is still much evidence that psychological elements like stress, anxiety or depression do play a significant role. There are several studies in the literature which only report the association of BMS with psychological factors. But to the best of our knowledge, there is no such case reported in the literature which has actually highlighted the management of such a case with psychogenic elements involved. In this case report, apart from discussing the role of psychological factors, the treatment of BMS with emphasis on counseling is also emphasized. Further, it is of interest to know that such patients with psychologically induced burning mouth syndrome have to be evaluated to their deepest details. Even their commonly overlooked gestures and habits like watching a particular television soap opera may be involved in their disease process. It can be concluded that psychological counseling in general dental practice can provide an effective cure for chronic oral burning sensation with psychological factors involved.